The digital competence of government public relations officer in Magelang City - Afrilia, Ascharisa Mettasatya; Rhizky, Deani Prionazvi; Putri, Wahyu Eka; Ratnasari, Eny (PRofesi Humas, 2023)
Background: Since new media is developing, it is important to examine new media literacy, especially in the era of 4.0. The government’s public relations also need new media literacy since the government needs to establish a harmonic relationship with the public to achieve sympathy, trust, teamwork, and support in government policy implementation. Purpose: This research aims to evaluate the digital competence of members of government public relations in the Magelang government apparatus forum. Methods: Digital competence is measured by questionnaires of functional and critical prosuming. This research uses a quantitative survey method. The survey includes the assessment of beliefs, opinions, and characteristics by using questionnaires. Questionnaires are used to collect the data by using items of questions for respondents. The research object is the government apparatus in Magelang, while the respondents are government public relations officers. The quantitative method is expected to comprehensively describe digital literacy by government public relations officers in the Magelang government apparatus. Data analysis uses descriptive statistics. Conclusion: Based on data analysis, members of government public relations in the Magelang government apparatus forum agree that they have functional and critical prosuming. Implications: This research implies local government of Magelang to improve new media literacy for local government public relations so the government can achieve the public relations objective of harmonic relationship establishment with the public.